The Influence of Work Motivation, Work Environment, and Career Development on Organizational Commitment Through Job Satisfaction as an Intervening Variable for Employees of Company: Pengaruh Motivasi Kerja, Lingkungan Kerja, dan Pengembangan Karir terhadap Komitmen Organisasi Melalui Kepuasan Kerja sebagai Variabel Intervening pada Perusahaan - Raihan, Azhar; Sumartik (Universitas Muhammadiyah Sidoarjo, 2023)
This research aims to find out the influence of work motivation on organizational commitment, work environment on organizational commitment, career development on organizational commitment, the influence of work motivation on job satisfaction, work environment on job satisfaction, career development on job satisfaction, job satisfaction to organizational commitment, work motivation to organizational commitment through job satisfaction as an intervening variable, the influence of the work environment. to organizational commitment through job satisfaction as an intervening variable, the influence of career development on organizational commitment through job satisfaction as an intervening variable in PT. Ramayana Lestari Sentosa Sidoarjo. This research method is Quantitative research, Population in this study 88 permanent employees of PT. Ramayana Lestari Sentosa at Jalan Diponegoro No. 2 Sidoarjo, Sampling technique using NonProbability Sampling Technique, The data source used in this study is primary data. Data analysis uses a quantitative research approach. The results of the study concluded that work motivation affects organizational commitment, work environment affects organizational commitment, career development affects organizational commitment, work motivation affects job satisfaction, work environment affects job satisfaction, career development affects job satisfaction, job satisfaction affects organizational commitment, job motivation has no effect on organizational commitment through Job satisfaction as an intervening variable, The work environment affects organizational commitment through job satisfaction as an intervening variable, career development has no effect on organizational commitment through job satisfaction as an intervening variable at PT Ramayana Lestari Sentosa Sidoarjo